ANALYSIS OF THE ACCOUNTING INFORMATION SYSTEM OF CASH RECEIPTS AND EXPENDITURES IN IMPROVING INTERNAL CONTROL AT THE KS PPS BMT NUSA UMMAT SEJAHTERA CILEUNYI BRANCH OFFICE - Rinda Andayani; Lina Yulianti; Ridwan Effendi (Gunung Djati Conference Series, 2025)
In the era of digital transformation, Islamic financial institutions are required to have reliable financial management systems to face increasing competition and the complexity of financial transactions. One of the essential elements is the Accounting Information System (AIS), which plays a role in accurately recording, processing, and reporting financial transactions. This study aims to analyze the implementation of AIS in cash management and its contribution to strengthening internal control at KSPPS BMT Nusa Ummat Sejahtera Cileunyi Branch. This research employs a descriptive method with a qualitative approach. Data were obtained through interviews, observations, and documentation. The results show that KSPPS BMT has implemented an online-based AIS using IBSS and Branchless software, which includes key components such as hardware, software, brainware, databases, procedures, and communication networks. This system supports accountability and efficiency in financial recording in accordance with Sharia principles. However, the implementation is not yet optimal due to challenges such as system disruptions, limited technology, and continued use of manual records. Internal control is also not fully effective due to a lack of professional staff, an informal organizational structure, and unclear task separation. Nevertheless, the presence of AIS has proven beneficial in monitoring transactions, improving the reliability of financial reports, and supporting audits and decision-making processes. Therefore, strengthening technological infrastructure and enhancing human resource competencies are key to optimizing AIS implementation in the future.